2013
DOI: 10.1111/xen.12063
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological findings in non‐human primate recipients of porcine renal xenografts: quantitative and qualitative evaluation of proteinuria

Abstract: The study of clinicopathological changes in cynomolgus monkey renal xenograft recipients provides a valid help in monitoring the health conditions in the post-transplant period. Moreover, the evaluation of UPC ratio and the use of SDS-AGE technique in urine samples of cynomolgus monkey renal xenograft recipients may be considered a valid, inexpensive, and less time-consuming method than more sophisticated techniques in monitoring proteinuria. Proteinuria and presence of low molecular weight (LMW) proteins were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Moreover, GalT-KO kidney function was markedly prolonged when a vascularized thymus co-transplantation was performed in baboon recipients of MGH GalT-KO kidneys, with survivals without rejection averaging 51 days and with some survivals up to 83 days (8,9). However, the graft survival of GalT-KO kidneys in non-human primates as reported by other groups were limited and most grafts were lost within 16 days following transplantation (10,11). …”
Section: Introductionmentioning
confidence: 89%
“…Moreover, GalT-KO kidney function was markedly prolonged when a vascularized thymus co-transplantation was performed in baboon recipients of MGH GalT-KO kidneys, with survivals without rejection averaging 51 days and with some survivals up to 83 days (8,9). However, the graft survival of GalT-KO kidneys in non-human primates as reported by other groups were limited and most grafts were lost within 16 days following transplantation (10,11). …”
Section: Introductionmentioning
confidence: 89%
“…However, Pintore et al reported that proteinuria and presence of low molecular weight proteins were consistently found in urine after kidney transplantation in a multitrangenic, including human decay accerlating factor (hDAF), GalT-KO pig-to-cynomologus model (52). In addition, we have a case of an hDAF/GalT-KO-to-cynomolgus monkey renal transplant using an anti-CD40L based regimen without vascularized thymic graft which developed proteinuria following kidney transplantation similar to baboon recipients of GalT-KO kidneys (Yamada et al, manuscript in preparation).…”
Section: Persistent Proteinuria Despite T-cell Unresponsivenessmentioning
confidence: 99%
“…However, although the use of the CRISPR/CAS9 technology has made the development of new lines of GalT-KO swine far easier than previously thought, the genes responsible for development of proteinuria has not been address by others. Recent data have found that incompatibility of a porcine CD47-baboon signal regulatory protein α (SIRP-α), which is an interspecies ligand-receptor interaction, induces activation of macrophages and phagocytosis in xenogeneic combinations (5256). Immune activation of the porcine podocyte leads to expression of CD80 which potentially downregulates SIRP-α and SMPDL-3b.…”
Section: Persistent Proteinuria Despite T-cell Unresponsivenessmentioning
confidence: 99%
See 2 more Smart Citations